Repair of lumbar incisional hernia using polypropylene mesh strip sutures – A case report - Deshpande, Anil (Int J Surg Case Rep, 2021)
INTRODUCTION: Lumbar hernias are considered rare and they constitute less than 1.5% of all abdominal wall hernias. CASE REPORT: Here we present a case of a 72-year-old female with a left flank swelling since 2-years diagnosed as a lumbar incisional hernia. This lumbar incisional hernia was repaired successfully using polypropylene mesh strip sutures. DISCUSSION: Many surgical techniques have been described for repair of LIH. Suture repair, mesh repair and myofascial flaps have been described for lumbar hernias. Repairing a lumbar hernia can be surgically challenging because of its proximity to bony structures, which can limit proper dissection and mesh overlap. We performed defect closure with PMSS. Patient has no recurrence after 2 years of follow up. CONCLUSION: In our case of left lumbar incisional hernia, defect closure with PMSS was an effective operation. This technique may also be effective in potentially contaminated settings due to reduced implant load. Further studies are required to understand its biomechanics and long-term outcomes.